The Holocaust and historical methodology - Stone, Dan 1971- Hrsg (Making sense of history, 2012)
The Holocaust and historical methodology / Dan Stone -- A world without Jews: interpreting the Holocaust / Alon Confino -- Holocaust historiography and cultural history / Dan Stone -- The invisible crime: Nazi politics of memory and postwar representations of the Holocaust / Dirk Rupnow -- The history of the Jews in the ghettos: a cultural perspective / Amos Goldberg -- National Socialism, Holocaust, and ecology / Boaz Neumann -- Bearing witness: theological roots of a new secular morality / Samuel Moyn -- Transcending history? Methodological problems in Holocaust testimony / Zoe Waxman -- Studying the Holocaust: is history commemoration? / Doris L. Bergen -- An integrated history of the Holocaust: some methodological challenges / Saul Friedlander -- Truth and circumstance: what (if anything) can be properly said about the Holocaust? / Hayden White -- Modernist Holocaust historiography: a dialogue between Saul Friedlander and Hayden White / Wulf Kansteiner -- The Holocaust and European history / Donald Bloxham -- Fascism and the Holocaust / Federico Finchelstein -- The Holocaust and world history: Raphael Lemkin and comparative methodology / A. Dirk Moses